Exploring Singapore legal information : a domain-analytic approach to law librarianship - Lin, Clement Zikai (Nanyang Technological University, 2021)
This dissertation aims to perform a sketch of the legal information domain in Singapore by employing the domain-analytic approach which was first proposed by Hjørland (1993). The domains of various disciplines, topics and communities have since been studied in the domain analysis literature of library and information science (LIS), but law remains one of the areas with limited contributions. By exploring this topic, the paper hopes to contribute to both (1) the general pool of domain analysis literature; as well as (2) to generate discourse as part of the process of building up the landscape of Singapore law librarianship, which is still presently in its nascent stages. Law librarianship, like health/medical librarianship, offers much potential for studies in domain analysis in LIS due to it being fairly established with its own set of unique domain-specific information norms and practices. This study therefore examines different key aspects of the legal information domain but with a specific focus on Singapore, a common law legal system. The dissertation explores the following aspects of the Singapore legal information domain: (1) its conceptual boundaries; (2) its historical underpinning; (3) the information sources and services; (4) the producers and users of legal information; and (5) prevailing legal information organization practices. In each of these sections, unique elements of the Singapore legal information domain are articulated through the domain-analytic approach. Through this exercise, the value of domain analysis as a systematic approach to mapping out a knowledge domain is demonstrated. This study finds that domain analysis exposes certain assumptions about the Singapore legal information domain as well as gaps in the current literature, on top of its role of providing structured roadmap for Singapore legal information professionals to learn about the domain. The insight generated from the dissertation may be relevant to law librarians, knowledge management personnel, information professionals, the legal fraternity and LIS academics. As an exploratory piece, it is hoped that it will spur further research in the terrain of Singapore law librarianship.